The hydrogen embrittlement sensitivity of duplex stainless steel with different phase fractions evaluated by in-situ mechanical testing (Fracture and Structural Integrity, 2019)
The influence of the austenite (γ) phase fraction on the hydrogen embrittlement of duplex stainless steel is investigated. Heat treatments are performed to create two duplex stainless steel specimens, containing 50% and 44% of austenite, respectively. Mechanical testing with and without hydrogen charging reveals that significant embrittlement occurs regardless of the austenite fraction. A higher austenite fraction results in a reduced ductility loss under the presence of hydrogen. Samples with a higher ferrite fraction are embrittled more due to their higher hydrogen diffusivity. In-situ tensile tests, interrupted at the ultimate tensile strength, show hydrogen-assisted cracks on the specimen surface both in austenite and ferrite and across the α/γ interface.
Keywords: Hydrogen embrittlement; Duplex stainless steel; In-situ mechanical testing